Reaksi Pasar atas Publikasi Laporan Keuangan Interim Diaudit Studi Empiris pada Perusahaan-Perusahaan yang Mempublik di Bursa Efek Indonesia - Irawan Irawan; Arif Makhsun (Jurnal Ilmiah ESAI, 2019)
This study was conducted on interim financial statements of companies included in the calculation of the KOMPAS 100 index on the Indonesia Stock Exchange (IDX) with the consideration that the companies' shares included in the KOMPAS 100 index on average per year control more than 75% in volume trade and market capitalization on the Indonesia Stock Exchange (IDX) so that it is considered the most widely traded stock. Hence, it is expected that many interested parties (especially active investors) of the interim financial report and use accounting information from the company in its investment decisions. The study was conducted on quarterly financial statements, mid-year financial reports and quarterly financial statements.The results of this study indicate that the market responds widely to the announcement of the Interim Financial Report I and Interim Financial Report II published by the issuer. On the other hand the market does not respond broadly to the announcement of the Interim Financial Report III published by the issuer.The involvement of auditors in interim financial reports in the form of reviews and complete audits does not have an impact on improving the quality of information on interim financial statements received by investors. This is demonstrated by the absence of differences in market reactions to the publication of interim financial statements.Keywords: Interim Financial Reports, Market Reactions